Effectiveness of Endoscopic Dilatation for Corrosive Oesophageal Strictures - Saad Hassan Khan, Muhammad Yasir Younas, Muhammad Azhar Waseem, Sonia Saleem, Sadia Jabbar, Asmat Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of study was to determine the efficacy after endoscopic dilatation in patients of corrosive intake. Study Design: It was descriptive case series Setting: Research was conducted at Medical Unit-III, Services Hospital, Lahore. Duration: Duration of study was 6 months from 1st November 2016 to 30th April 2017. Material and Methods: This study involved 150 patients of age 18-65 years with corrosive intake and dysphagia score ≥ 2. A written informed consent was taken from each patient. Results: Total 150 patients were added in the study. Out of these, 118 patients (78.7%) were females while 32 (21.3%) were males. The age of patient ranged from 18 to 48 years with a mean of 26.72 ±5.61. One hundred thirty two patients (88 %) showed improvement in dysphagia while 18 patients (12 %) did not show any improvement. Efficacy calculated by chi- square test which showed p-value of .000 (statistically significant) Conclusion: 150 patients with dysphagia score ≥ 2 were added in study and dilated with Savary-Gilliard dilator. 132 patients showed improvement in dysphagia with p-value of .ooo (statistically significant).